Non-parametric approach to measure efficiency level of paddy farmers in Kedah - Zabidi, Nerda Zura; Baten, Md Azizul; Mat Kasim, Maznah; Ramli, Razamin (Universiti Teknikal Malaysia Melaka, 2016)
Rice is the basic food, most important source of employment and income as well as the main cultivation activity of paddy farmers in northern region of Malaysia.The efficiency of rice production has been of longstanding interest to the responsible organization in agriculture.This paper attempts to study the efficiency of paddy farmers in Kedah using Data Envelopment Analysis model.Four districts have been selected with the total respondents of 200. Overall average performance of paddy farmers is 0.787.The paddy farmers in Kepala Batas are the most efficient followed by Kubang Pasu, Kerpan and Kubang Pasu. Only few paddy farmers in Kubang Sepat, Kubang Pasu and Kerpan are showing very low relative performances,, on the other hand, not a single farmer in Kepala Batas district shows such low performance. By knowing the existing efficiency level of paddy farmers, the government can take viable plans or actions to increase the efficiency of paddy farmers in Kedah.